A natural freshwater origin for two chlamydial species, Candidatus Piscichlamydia salmonis and Candidatus Clavochlamydia salmonicola, causing mixed infections in wild brown trout ( Salmo trutta ) - Heike Schmidt‐Posthaus; Adam Polkinghorne; Lisbeth Nufer; Andrea Schifferli; Dieter R. Zimmermann; Helmut Segner; Pascale Steiner; Lloyd Vaughan (Environmental Microbiology, 2012)
Summary Gill disease in salmonids is characterized by a multifactorial aetiology. Epitheliocystis of the gill lamellae caused by obligate intracellular bacteria of the order Chlamydiales is one known factor; however, their diversity has greatly complicated analyses to establish a causal relationship. In addition, tracing infections to a potential environmental source is currently impossible. In this study, we address these questions by investigating a wild brown trout ( Salmo trutta ) population from seven different sites within a Swiss river system. One age class of fish was followed over 18 months. Epitheliocystis occurred in a site‐specific pattern, associated with peak water temperatures during summer months. No evidence of a persistent infection was found within the brown trout population, implying an as yet unknown environmental source. For the first time, we detected ‘ Candidatus Piscichlamydia salmonis’ and ‘ Candidatus Clavochlamydia salmonicola’ infections in the same salmonid population, including dual infections within the same fish. These organisms are strongly implicated in gill disease of caged Atlantic salmon in Norway and Ireland. The absence of aquaculture production within this river system and the distance from the sea, suggests a freshwater origin for both these bacteria and offers new possibilities to explore their ecology free from aquaculture influences.